JURIDICAL REVIEW OF THE IMPLEMENTATION OF A PARTICULAR TIME AGREEMENT BASED ON LAW NUMBER 13 OF 2003 CONCERNING MANPOWER - Bunadi, Bunadi; Miharja , Marjan (IBLAM LAW REVIEW, 2021)
Industrial relations disputes are common in many companies. The dismissal process is often not in accordance with the provisions of labor regulations, one of which is regarding the dismissal of PKWT / contract workers. The formulation of the problems that the author discusses in this thesis are (1) What is the role of trade unions in fighting for dismissal disputes with PKWT / Contract workers? (2) Is the Application of a Fixed Time Work Agreement (PKWT) in accordance with the provisions of Law Number 13 Year 2003 concerning Manpower? The research method used in this research is juridical normative, namely looking at the law as a written norm made and promulgated by an authorized official or institution, the nature of descriptive analytical research is a study to obtain an overview of the main object of the problem being researched. The results showed that, the role of trade unions in companies in fighting for dismissal disputes against PKWT / Contract workers in accordance with Law no. 2 of 2004 concerning PPHI article 6 in conjunction with article 8 in conjunction with article 81, namely by conducting a bipartite effort between the labor union and the company, because the bipartite effort failed, then submitted a mediation request to the Manpower Office. The mediation attempt still failed and subsequently filed a lawsuit for dismissal disputes at the Industrial Relations Court, although it was unsuccessful. The application of a fixed-term employment agreement (PKWT) is contrary to the provisions of Law number 13 of 2003 concerning Manpower Article 59 paragraphs (1), (2), and (7). In addition, the PHI Judge in deciding the case did not reflect a sense of justice and ignored the evidence presented by the plaintiff (the worker). This problem should not have occurred, if the company obeyed and understood the labor regulations regarding workers who could be promised under a non-permanent contract or PKWTT.